Care Technologies for Ageing Societies An International Comparison - Hamblin, Kate; Lariviere, Matthew (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Technology is quickly becoming an integral part of care systems across the world and is frequently cited in policy discourse as pivotal for solving the 'crisis' in care and delivering positive outcomes. Exploring the role of technology in Europe, Canada, Australia and Japan, this book examines how technology contributes effectively to the sustainability of these different care systems, which are facing similar emergent pressures, including increased longevity, falling fertility and the consequences of the COVID-19 pandemic. It considers the challenges and opportunities of embedding technologies in care systems and the subsequent outcomes for older and disabled service users, carers and the care workforce.